Analyser les pratiques d’enseignement-apprentissage de la lecture des textes littéraires : quelle modélisation pour quels enjeux ? - Jean-Louis Dufays (Recherches en Éducation, 2017)
Conceived as an essay of theoretical discussion, the article starts from the observation that the analysis of teaching-learning practices in the reading of literary texts is torn between two types of competing modeling: one centered on the expected activity of the teacher and / or students, the other centered on observing actual practices. A similar opposition can be established in the way the teachers model their own activity and that of their students. It appears, however, that, regardless of the analysis plan considered, the tension between these two models is not sufficient to account for the complexity of the teaching-learning activities and the relation to the literary texts. The article argues, therefore, with supporting examples, in favor of a median position based on two notions that make one think of the relation to literary texts in a dialectical way: the notion of interpretative community and the notion of literary reading.